Maternal Risk Factors Associated with Term Low Birth Weight in Jigme Dorji Wangchuck National Referral Hospital, Bhutan - Wangdi, Phurpa; Tenzin, Karma; Gyamtsho, Sonam; Tshomo, Ugyen; Bhutia, Pema Choden; Wangden, Tshering; Dorji, Phurb (Nepal Journal of Obstetrics and Gynaecology, 2020)
Aims: To investigate the association of various maternal factors and associated medical conditions during pregnancy with low birth weight (LBW) at term in neonates. Methods: An unmatched case control study was done involving 150 cases (mothers who delivered singleton baby at term weighing less than 2500g) and 150 controls (mothers who delivered singleton baby at term weighing ≥2500g) in Jigme Dorji Wangchuck National Referral Hospital from 2018 to 2019. Consecutive and systematic sampling methods were used to select case and control respectively. Student unpaired t-test was used to test the differences between the control and case means for various factors. Odds ratios were used to assess the role of various factors on low birth weight Results: This study found maternal height, weight gain during pregnancy, time of first antenatal visit and hypertension during pregnancy as the independent predictors of low birth weight. Conclusions: Targeted interventions such as improving maternal weight gain during pregnancy, empowering mothers to come early for their first antenatal care and optimising gestational hypertension can help to prevent low birth weight. Keywords: Bhutan, case control study, low birth weight, risk factors, singleton pregnancy.